BIO-EFFICACY OF INSECTICIDES AGAINST CERATOVACUNA LANIGERA ZEHNTNER AND SELECTIVITY TO DIPHA APHIDIVORA MEYRICK IN SUGARCANE - R. Sheeba Jasmine; B. Rajendran (Journal of Sugarcane Research, 2020)
Selected insecticides were evaluated for effectiveness against the sugarcane woolly aphid,Ceratovacuna lanigera Zehntner (Homoptera: Aphididae) and safety to the predator Dipha aphidivora Meyrick (Lepidoptera: Pyralidae). Observations of aphid and predator mortality at three, seven and 15 days after spraying showed that thiamethoxam 25 WG @ 0.005% was highly effective against the aphid with the highest yield followed by acetamiprid 20 SP @ 0.004% which were relatively safe to Dipha larvae. Buprofezin 25 SC @ 0.025% recorded the highest population of Dipha and carbosulfan 25 EC @ 0.05% registered the lowest population three days after spraying.